Exploring Hindu Eco-Ethics in School-Based Zero Waste Initiatives: Implications for Student Character Education in Denpasar - Sutriyanti, Ni Komang; Andre Suhardiana , I Putu; Darma Permana, I Dewa Gede (Jurnal Kajian Bali (Journal of Bali Studies), 2025)
The lack of waste management awareness leading to waste accumulation has prompted elementary schools in Denpasar to implement a Hindu Eco-ethics-based Zero Waste program. Using a qualitative research method with a field study approach, this study aims to explore and analyze the program’s implementation, challenges, and its implications for strengthening student character. Primary data was collected through interviews and observations, supported by secondary data from literature reviews and documentation. Through qualitative data analysis using the Miles and Huberman approach and verified with triangulation techniques, the findings reveal that the Zero Waste program focuses on systematic efforts to enable school communities to manage their own waste. The challenges include awareness gaps, infrastructure limitations, and insufficient external support. Despite these obstacles, the program shows positive impacts on student character building. This research provides guidelines for waste management program development and serving as a reference for future environmental studies.